2013
DOI: 10.3133/ofr20121234
|View full text |Cite
|
Sign up to set email alerts
|

Application of a hydrodynamic and sediment transport model for guidance of response efforts related to the Deepwater Horizon oil spill in the Northern Gulf of Mexico along the coast of Alabama and Florida

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment, visit http://www.usgs.gov or call 1-888-ASK-USGS.For an overview of USGS information products, including maps, imagery, and publications, visit http://www.usgs.gov/pubprodTo order this and other USGS information products, visit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 10 publications
0
18
1
Order By: Relevance
“…SOAs resulting from this spill were typically found on the range of 0.5–8 cm in diameter, while SOMs spanned up to several meters in length and were up to 20 cm thick (Dickey & Huettel, ; Hayworth et al, ; Michel et al, ). Field observations of SOAs and SOMs revealed that these aggregates were formed with weathered oil and either coarse sediment (such as the sand that is found along Florida and Alabama beaches) or large amounts of finer sediment (such as the clay that is found along some Louisiana beaches), and they are typically found either atop the sediment layer, buried within the sediment, or washed up to rest in the supratidal zone (Dalyander et al, ; OSAT‐2, ; OSAT‐3, ; Plant et al, ). SOAs are often referred to colloquially as tar balls; however, in contrast to traditional pelagic tar balls, which are rubbery with little or no sediment incorporated, SOAs are a type of benthic agglomerates that have sand and/or clay not only on the outer surface but also throughout the interior (Hayworth et al, ).…”
Section: Formationmentioning
confidence: 99%
See 4 more Smart Citations
“…SOAs resulting from this spill were typically found on the range of 0.5–8 cm in diameter, while SOMs spanned up to several meters in length and were up to 20 cm thick (Dickey & Huettel, ; Hayworth et al, ; Michel et al, ). Field observations of SOAs and SOMs revealed that these aggregates were formed with weathered oil and either coarse sediment (such as the sand that is found along Florida and Alabama beaches) or large amounts of finer sediment (such as the clay that is found along some Louisiana beaches), and they are typically found either atop the sediment layer, buried within the sediment, or washed up to rest in the supratidal zone (Dalyander et al, ; OSAT‐2, ; OSAT‐3, ; Plant et al, ). SOAs are often referred to colloquially as tar balls; however, in contrast to traditional pelagic tar balls, which are rubbery with little or no sediment incorporated, SOAs are a type of benthic agglomerates that have sand and/or clay not only on the outer surface but also throughout the interior (Hayworth et al, ).…”
Section: Formationmentioning
confidence: 99%
“…Numerical modeling tools have been used to better understand and predict the causes, hindrances, and patterns of the mobility of Deepwater Horizon SOAs along the Alabama/Florida coast based on different currents and wave conditions (Dalyander et al, ; OSAT‐3, ; Plant et al, ). The various shoreline conditions were used to account for changes in wave height, direction, and period, as well as wind speed and direction.…”
Section: Formationmentioning
confidence: 99%
See 3 more Smart Citations